1980
DOI: 10.1111/j.1440-169x.1980.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Ion-Requiring Step in Fertilization of Sea Urchins*

Abstract: The magnesium ion-requiring step in fertilization of sea urchins was investigated. When eggs were inseminated in Mg-free sea water, several spermatozoa were found to bind to each egg surface with their reacted acrosomes without elevation of fertilization membrane. The number of binding jelly-treated spermatozoa to an egg did not differ regardless of the presence or virtual absence of magnesium ions. Although fertilization did not occur in Ca, Mg-deficient sea water (CM-deficient SW) even when jelly-treated spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…A similar effect was observed by inseminating eggs in Mg z+ -free sea water (Sano et al 1980). Quercetin at 100^M blocks sperm incorporation in oocytes; furthermore, despite apparently normal attachments, the spermatozoa do not induce any electrical changes across the oocyte plasma membrane.…”
Section: Electrical Eventssupporting
confidence: 60%
“…A similar effect was observed by inseminating eggs in Mg z+ -free sea water (Sano et al 1980). Quercetin at 100^M blocks sperm incorporation in oocytes; furthermore, despite apparently normal attachments, the spermatozoa do not induce any electrical changes across the oocyte plasma membrane.…”
Section: Electrical Eventssupporting
confidence: 60%
“…In previous papers we have reported that magnesium ions in seawater are required for fertilisation of sea urchins (Sano & Mohri, 1976Sano et al, 1980;Mohri et al, 1982). In the absence of Mg 2 * the fertilisation rate was reduced to almost nil.…”
Section: Introductionmentioning
confidence: 89%
“…The sperm head was moving in 3CMFSW, but abruptly came to a standstill, perpendicular to the egg surface, immediately after addition of Mg 2+ . Even though a spermatozoon other than that being observed in focus caused the elevation of the fertilisation membrane in the other six cases, it is quite likely that they also had already attached to the egg surface in the absence of Mg 2+ (see also Sano et al, 1980). Could the sperm attached to the egg in MFSW resume entry into the egg when the egg was activated by some other means?…”
Section: Microscopic Observationsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that in the presence of Quercetin, an ATPase inhibitor, spermatozoa attach to sea-urchin eggs and undergo the acrosome reaction; however, sperm incorporation is inhibited (Eckberg & Perotti, 1983). A similar effect was observed by inseminating eggs in Mg z+ -free sea water (Sano et al 1980). Quercetin at 100^M blocks sperm incorporation in oocytes; furthermore, despite apparently normal attachments, the spermatozoa do not induce any electrical changes across the oocyte plasma membrane.…”
Section: Electrical Eventsmentioning
confidence: 92%